Migration pattern of Desi sheep of Gujarat – a note - GR Gowane; LLL Prince,; C Paswan; RC Sharma; SMK Naqvi (Journal of Livestock Biodiversity, 2025)
The study was conducted to understand the migration pattern of the local sheep of Gujarat commonly known as Desi or Patanwadi sheep. It was observed that the locks of sheep are truly migratory and follow a shuttling pattern of migration depending on the availability of the feed resources and rainfall. Detailed survey and tracking of migratory locks in Surendranagar district revealed that, Sayla, Muli and Chotila blocks (taluqua) harbours a number of villages where Bharwad or Rebari communities are mostly associated with migratory sheep husbandry practices. The sheep shifts from Saurashtra, Kutch and Bhuj region post Diwali to Ahmedabad and surrounding region and at the onset of monsoon again return to the dry region of Saurashtra, Kutch and Bhuj to avoid excess rainfall and to secure grazing resources. Geographical condition, soil make up, rainfall pattern, etc. play a signi icant role in deciding the migratory route for nomads